Enhanced power sharing and voltage regulation for islanded nano-satellite DC microgrids in spinning flight scenarios - Khalil Louassaa; Josep M. Guerrero; Baseem Khan; Muhammad Zain Yousaf; Mohamed Ali Zdiri; Liu Zhang; Rajkumar Sivanraju (Scientific Reports)
Abstract The Small Satellite (SmallSat) industry has advanced significantly, with CubeSats playing crucial roles in Earth observation and scientific research due to their low cost and modularity. The Electrical Power System (EPS) is a critical subsystem that integrates photovoltaic sources, energy storage, and power converters to ensure reliable operation. However, EPS design faces challenges from strict size limitations, high power density requirements, and extreme space conditions, demanding robust control strategies. This paper presents a hierarchical control approach for islanded nano-satellite microgrids under real flight conditions. The dual-layer architecture combines a proportional-integral (PI) controller for secondary voltage regulation and a non-singular terminal sliding mode (NTSM) controller for primary disturbance rejection. The solution provides four key advantages: (1) robust handling of dynamic operational conditions including sudden constant power load variations, source fluctuations, and islanding/connection mode transitions; (2) decoupled control architecture separating high-level power management from fast local regulation; (3) optimized computational efficiency for onboard processing constraints; and (4) enhanced environmental robustness through NTSM’s inherent stability in extreme thermal/radiation conditions. Comprehensive validation through stability analysis, simulations, and experimental testing demonstrates superior performance versus conventional methods, with significant improvements in transient response speed, steady-state error reduction, and disturbance rejection capability. The proposed framework offers a practical solution for nano-satellite power management, directly addressing the unique constraints of space applications while maintaining system reliability and efficiency under dynamic operational conditions.